High Utilization of Composite Magnesium Metal Anodes Enabled by a Magnesiophilic Coating - Li, Yuanjian; Yang, Gaoliang; Sun, Shengnan; Zhang, Chang; Lim, Carina Yi Jing; Wong, Andrew Jun Yao; Lieu, Wei Ying; Sofer, Zdenek; Ng, Man-Fai; Liu, Wei; Seh, Zhi Wei (Nano letters, 2022)
Metallic magnesium is a promising high-capacity anode material for energy storage technologies beyond lithium-ion batteries. However, most reported Mg metal anodes are only cyclable under shallow cycling (≤1 mAh cm-2) and thus poor Mg utilization (<3%) conditions, significantly compromising their energy-dense characteristic. Herein, composite Mg metal anodes with high capacity utilization of 75% are achieved by coating magnesiophilic gold nanoparticles on copper foils for the first time. Benefiting from homogeneous ionic flux and uniform deposition morphology, the Mg-plated Au-Cu electrode exhibits high average Coulombic efficiency of 99.16% over 170 h cycling at 75% Mg utilization. Moreover, the full cell based on Mg-plated Au-Cu anode and Mo6S8 cathode achieves superior capacity retention of 80% after 300 cycles at a low negative/positive ratio of 1.33. This work provides a simple yet effective general strategy to enhance Mg utilization and reversibility, which can be extended to other metal anodes as well.
Keywords: High utilization; Magnesium batteries; Magnesium metal anodes; High reversibility; Magnesiophilic coating